The Reynold’s number effect in high swirling flow in unconfined burner - Norwazan, A. R. (Penerbit UTM Press, 2015)
The numerical simulations of swirling turbulent flows in isothermal condition in combustion chamber of burner were investigated. The aim is to characterize the main flow structures and turbulence in a combustor that is relevant to gas turbines. Isothermal flows with different inlet flow velocities were considered to demonstrate the effect of radial velocity. The inlet velocity, Uo is varied from 30 m/s to 60 m/s represent a high Reynolds number up to 3.00 X 105. The swirler was located at the upstream of combustor with the swirl number of 0.895. A numerical study of non-reacting flow in the burner region was performed using ANSYS Fluent. The Reynolds–Averaged Navier–Stokes (RANS) approach method was applied with the standard k-? turbulence equations. The various velocity profiles were different after undergoing the different inlet velocity up to the burner exit. The results of velocity profile showed that the high U0 give better swirling flow patterns.